1998
DOI: 10.1111/j.1740-8261.1998.tb01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Perinephric Pseudocysts and Polycystic Kidneys in a Ferret

Abstract: A 3-year-old castrated male domestic ferret was evaluated for abdominal distention. Survey lateral and dorsoventral abdominal radiographs were made. There were two soft tissue radiopacities consistent with grossly enlarged kidneys displacing small bowel and colon cranially, ventrally and caudally. Abdominal ultrasound was performed and revealed bilateral perinephric pseudocysts and polycystic kidneys. The perinephric pseudocysts were found to be dilated renal capsules on exploratory surgery and were drained. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
1
4
0
3
Order By: Relevance
“…25 Similar to the human form, a mutation on the PKD1 gene causes the majority of adult PKD in cats 13,19 whereas autosomal-dominant PKD in Bull Terriers is likely not associated with a mutation in the canine PKD1 or PKD2 genes. 22,23 Similar alterations are also reported in adult ferrets 6,28 and horses 1,5,29 but the genetic background in these species is unknown.…”
Section: Introductionsupporting
confidence: 56%
“…25 Similar to the human form, a mutation on the PKD1 gene causes the majority of adult PKD in cats 13,19 whereas autosomal-dominant PKD in Bull Terriers is likely not associated with a mutation in the canine PKD1 or PKD2 genes. 22,23 Similar alterations are also reported in adult ferrets 6,28 and horses 1,5,29 but the genetic background in these species is unknown.…”
Section: Introductionsupporting
confidence: 56%
“…6, 8, 9 Perinephric pseudocysts are uncommon lesions in cats and are rare in dogs, ferrets, pigs, and humans. 4, 7, 1113 This manuscript characterizes a unilateral perinephric pseudocyst secondary to hydronephrosis in a C57BL/6J mouse.…”
mentioning
confidence: 99%
“…6,8,9 Perinephric pseudocysts are uncommon lesions in cats and are rare in dogs, ferrets, pigs, and humans. 4,7,[11][12][13] This manuscript characterizes a unilateral perinephric pseudocyst secondary to hydronephrosis in a C57BL/6J mouse.A 9-month-old female C57BL/6J mouse, part of a control group of an impending research study, showed progressive abdominal distension over 1 week's time. The mouse was euthanatized with carbon dioxide, and an incision of the abdomen showed a distended left kidney.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Die Disposition des Frettchens zur Ausbildung multipler Nierenzysten ist aus Sektionsstatistiken bekannt (3). Ihr sonographischer Nachweis wurde bisher allerdings erst in einem Fall beschrieben (26). Nach einer neueren Untersuchung geht man bisher davon aus, dass ca.…”
Section: /184unclassified